Pengaruh Kompetensi, Komunikasi Interpersonal, dan Kualitas Pelayanan Kesehatan terhadap Kepuasan Pasien di Puskesmas Pembantu Lubang Buaya, Jakarta Timur - Hermina Nurmalita Sari; Enjang Sudarman; Nurwulan Kusuma Devi; Zulkifli Rangkuti; Eddy Hermawan Hasudungan; bambang nurakhim (Lembaga Pengembangan Kinerja Dosen, 2025)
The success of Puskesmas services is highly dependent on the quality of services provided, especially in an effort to meet patient expectations and satisfaction. This study is focused on exploring the relationship between the competence of medical personnel, interpersonal communication skills, and service quality with patient satisfaction levels at the Lubang Buaya Auxiliary Health Center, East Jakarta. Primary health services have a strategic role in maintaining public health, so understanding the determinants of patient satisfaction is crucial. This study uses a quantitative approach with a correlational design. A total of 100 respondents were selected through a total sampling technique, and data was collected using a questionnaire instrument that had been tested for validity and reliability. Data analysis was carried out using multiple linear regression, accompanied by a t-test, F test, and a determination coefficient to assess the strength and contribution of each variable to patient satisfaction. The results of the analysis showed that the three variables—competence of health workers, interpersonal communication, and quality of service—significantly affected patient satisfaction, both partially and simultaneously, with an adjusted R² value of 0.842. This figure indicates that about 84.2% of the variation in patient satisfaction can be explained by these three factors. These findings strengthen the evidence that increasing professional capacity, mastering effective communication skills, and improving service quality are the keys to the success of Puskesmas in building public trust and loyalty. The practical implication of this study is the need to develop a sustainable training program for health workers, including the development of technical competencies and soft skills. In addition, the internal policies of the Puskesmas must be directed at the formation of a service culture that is responsive, empathetic, and oriented to the needs of patients.